FACTORS INFLUENCING THE CHOICE OF FEMALE STERILIZATION AMONG WOMEN OF REPRODUCTIVE AGE IN BOJONGGEDE DISTRICT, BOGOR REGENCY - Arimurti, Jazzy Dwi; Herbawani, Chahya Kharin; Hanifah, Laily; Ardhiyanti, Lusyta Puri (Badan Kependudukan Dan Keluarga Berencana Nasional, 2024)
The prevalence of female sterilization as a contraceptive method is significantly low in Bojonggede, Bogor Regency. Out of the 45,000 couples, merely 3% of women have chosen sterilization. This study aims to identify the factors influencing the choice of female sterilization among women of reproductive age in Bojonggede, Bogor Regency. The research utilized a quantitative study with a cross-sectional approach. The data was gathered through interviews using questionnaires distributed to 171 samples selected through purposive sampling. The Chi Square test was used to analyze the data aiming to examine the relationship between all of the independent variables concerning the choice of female sterilization among women of reproductive age in Bojonggede, Bogor Regency. The findings of this study found a significant association between age, parity, perceived susceptibility, perceived severity, perceived benefit, perceived barriers, and cues to action based on husband support with the choice of female sterilization in Bojonggede. Hence, it is recommended to conduct unrestricted sterilization policy in response to increase the female sterilization selection rate in Bojonggede and ensure that all women are provided equally to access sterilization regardless their age and parity.